Surveillance of adverse events associated with 145 000 doses of COVID-19 vaccines in a Brazilian municipality - Paulo Ricardo Martins-Filho; Ricardo Ruan Rocha Santana; Taise Ferreira Cavalcante; Waneska de Souza Barboza; Mércia Feitosa de Souza; Marco Aurelio de Oliveira Góes; Ângela Marinho Barreto Fontes; Marcia Estela Lopes da Silva; Diego Moura Tanajura (Pan American Health Organization, 2022)
There is a lack of real-world surveillance studies on reports of adverse events associated with COVID-19 vaccination, as well as comparative analyses of adverse events from vaccines with different platforms. This observational, descriptive, retrospective study based on secondary data describes the adverse events following immunization (AEFIs) related to the first 145 000 doses of COVID-19 vaccines delivered in Aracaju municipality, Sergipe state, northeast Brazil. Records of AEFIs were collected using the e-SUS Notifica database for January 19 to April 30, 2021. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated for AEFIs and the type of COVID-19 vaccine, either CoronaVac (Sinovac-Butantan) or Oxford-AstraZeneca (Fiocruz). A total of 474 AEFIs (32.7 events/10 000 doses) from 254 individuals were reported and analyzed, and all of them were classified as non-serious. There was an association between the use of the CoronaVac vaccine and headache (OR = 2.1; 95% CI: 1.4-3.2), pain at the injection site (OR = 9.6; 95% CI: 3.9-23.8), lethargy (OR = 5.2; 95% CI: 1.8-14.8), fatigue (OR = 10.1; 95% CI: 2.4-42.3), diarrhea (OR = 4.4; 95% CI: 1.5-12.5) and cold-like symptoms (OR = 8.0; 95% CI: 1.9-34.0). However, the proportion of individuals reporting fever was higher among those who received the Oxford-AstraZeneca vaccine (OR = 3.1; 95% CI 1.5-6.4). This population-based observational study strengthens the evidence for the safety and tolerability of the CoronaVac and Oxford-AstraZeneca vaccines used against COVID-19.